P.-P.G. PRZHETSLAVSKY ON THE PEOPLES OF THE NORTHERN CAUCASUS: FORMATION OF VIEWS AND INFORMATIONAL VALUE - Tlepcok, Ruslan Aslanovic (History, Archeology and Ethnography of the Caucasus, 2026)
This article provides a source-critical analysis of the journalistic and ethnographic legacy of P.-P.G. Przhetslavsky, a career military officer whose works serve as a representative historical source on the period of the Northern Caucasus’s incorporation into the Russian Imperial system. Based on a comprehensive study of his works, including the essay Dagestan: Its Manners and Customs and diary entries from his service as a bailiff to Imam Shamil in Kaluga, the author identifies the dual nature of this legacy. On one hand, the study highlights the significant informative value of Przhetslavsky’s writings. His detailed descriptions of administrative structures, economic activities (terrace farming, animal husbandry, and handicrafts), statistical data, elements of daily life (housing, food, clothing), and customary law laid the foundation for subsequent ethnographic and historical research. These materials preserve unique data regarding the transformation of North Caucasian society following the Caucasian War. On the other hand, the article provides a reasoned argument regarding the author’s strong bias and subjectivity, which is particularly evident in his contentious relationship with Shamil. The use of evaluative clichés (such as “savage peoples”), the intentional disparagement of the Imam, and the contextual distortion of facts (extending even to inaccurate citations of the Quran) demonstrate Przhetslavsky’s rigid, pro-government stance. This perspective was shaped by his official status and his conviction in Russia’s “civilizing mission.” The study concludes that, despite an inevitable ideological bias, Przhetslavsky’s works remain vital historical documents. Their critical analysis allows researchers not only to reconstruct various aspects of life among the peoples of Dagestan but also to understand the mechanisms behind the formation and function of imperial knowledge regarding the Caucasus – a key objective of contemporary Caucasian Studies.